Interchange : The Emirates Fine Art Society 24th Annual Exhibition. - Exhibition. Interchange : The Emirates Fine Art Society 24th Annual Exhibition (Sharjah : Emirates Fine Art Society Sharjah Sharjah Art Museum Sharjah, 2005)
Dweik, Yousef ; Khazendar, Wafa ; Al-Haddad, Wesam ; Saife, Huda Saeed ; Idrees, Hiba ; Asad, Nuha ; Mekki, Najat ; Abdullah, Nasser ; Aldraihim, Nadia A. ; Bushlbi, Moza ; Cader Al Ali, Mura Abdul ; Hesso, Mahmoud ; Kazem, Mohammed ; Abdulla Abu Lyhiya, Mohammad
biog. per kunstenaar
Arabisch
Engels
boek